ANALISIS KINERJA KEUANGAN DITINJAU DARI SEGI LIKUIDITAS, STRUKTUR MODAL DAN PROFITABILITAS PADA PERUSAHAAN PUBLIK SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEJ PERIODE 2000-2004 - Basri Zein; Fahri Miraza (Jurnal Telaah dan Riset Akuntansi, 2008)
The objective of research is to identify the development of financial performance viewed from liquidity, capital structure, and profitability on public companies from miscellaneous industry sector that listed in Jakarta Stock Exchange during period 2000-2004.     Selecting of sample is done by purposive sampling method that it is judgment sampling under condition : 1) public companies from miscellaneous industry sector that listed in Jakarta Stock Exchange during period 2000-2004; 2) Financial report is limited on balance and income statement of public companies from miscellaneous industry sector that listed in Jakarta Stock Exchange during period 2003-2004 that they are available completely in library of Jakarta Stock Exchange.     Descriptive statistic is used to see the development of financial performance viewed from liquidity, capital structure, and profitability on public companies from miscellaneous industry sector that listed in Jakarta Stock Exchange during period 2000-2004; and Kruskal-Wellis statistic is used to see if there is significant difference of financial performance viewed from liquidity, capital structure, and profitability on public companies from miscellaneous industry sector that listed in Jakarta Stock Exchange during period 2000-2004.     Result of research shows financial performance of public companies from micellaneous industry sector that listed in Jakarta Stock Exchange during period 2000-2004 viewed from liquidity, capital structure, and profitability (ROI) are not good except profitability (REO). Result of research also shows during period 2000-2004 there are not significant difference of financial performance viewed from liquidity, and capital structure on public companies from miscellaneous industry sector, except viewed from profitability (ROI and ROE). Keyword : Financial Performance, Liquidity, Capital Structure, and Profitability